Crescimento, produção, trocas gasosas e qualidade de Beta vulgaris L. com águas salinas e silício via foliar e solo. - Melo Filho, José Sebastião de (2019)
Beet is one of the most nutrient rich vegetables (bioactive compounds, folic acid and potassium). There are few studies of this culture under conditions of irrigation with saline waters. Irrigation in agriculture is a viable alternative due to water scarcity and natural resources. The plants do not tolerate high levels of salts, however, salt stress attenuators presents a strategy to allow the use of saline waters in the semi-arid region. In regions with low rainfall rates, saline stress promotes physiological changes in plants, affecting crop productivity. The objective of this work was to evaluate the development, production, gas exchanges, post-harvest of beta vulgaris L. irrigated with salt water and silicon. The research was conducted in a randomized block design, in a 5 x 5 factorial, referring to five levels of electrical conductivity of irrigation water (CEa): (0.5, 1.3, 3.25, 5.2 and 6, 0 dS m-1), and five doses of silicon (0.00, 2.64, 9.08, 15.52 and 18.16 mL L-1), combined according to the Experimental Central Composite Box matrix, with four replicates and three plants per plot. Growth, gas exchange, chlorophyll, fluorescence, production and post-harvest analyzes were performed. The data were submitted to analysis of variance, regression and the repeated evaluations in time by mixed model. Leaf silicon application did not influence beet cultivation, nor did it attenuate the salinity, but the plants that received application showed higher photosynthetic pigment contents. Increasing ECa of irrigation water reduced beet growth and yield, but chlorophyll, biomass and fluorescence indices were not influenced by salinity. The CEa of irrigation water above 0.50 dS m-1 is sufficient to adversely affect the beet crop and the dose of 9.08 ml L-1 of silicon is the most recommended for application. Irrigation with water of 6.0 dS m-1 promotes better tuber beet quality. Pre-harvest fertilizations with silicon, applied via soil or foliar, improved the post-harvest quality of the beet. Irrigation with salt water inhibited the gas exchange of beet plants.